2011
DOI: 10.1007/s12640-011-9286-3
|View full text |Cite
|
Sign up to set email alerts
|

Ether-à-go-go 1 (Eag1) Potassium Channel Expression in Dopaminergic Neurons of Basal Ganglia is Modulated by 6-Hydroxydopamine Lesion

Abstract: The ether à go-go (Eag) gene encodes the voltage-gated potassium (K(+)) ion channel Kv10.1, whose function still remains unknown. As dopamine may directly affect K(+) channels, we evaluated whether a nigrostriatal dopaminergic lesion induced by the neurotoxin 6-hydroxydopamine (6-OHDA) would alter Eag1-K(+) channel expression in the rat basal ganglia and related brain regions. Male Wistar rats received a microinjection of either saline or 6-OHDA (unilaterally) into the medial forebrain bundle. The extent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…In situ hybridization studies have detected KCNH1 transcripts predominantly in the hippocampus, cerebral cortex, dopaminergic neurons of basal ganglia, and olfactory bulb and granular layer of the cerebellum of adult rats [4,1012]. KCNH1 channels may also be involved in sensory functions of auditory transduction and phototransduction.…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridization studies have detected KCNH1 transcripts predominantly in the hippocampus, cerebral cortex, dopaminergic neurons of basal ganglia, and olfactory bulb and granular layer of the cerebellum of adult rats [4,1012]. KCNH1 channels may also be involved in sensory functions of auditory transduction and phototransduction.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study using the 6-OHDA model of Parkinson's disease revealed that dopaminergic cells in the nigrostriatal pathway express Eag1 (11). 6-OHDA-injured animals presented a decrease in Eag1-positive cells proportional to the dopaminergic neuronal loss in the nigrostriatal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of p53, which results in cell cycle arrest or apoptosis, reduced the expression of Eag1 channel (9). Previous studies using the 6-hydroxydopamine (6-OHDA) model of Parkinson's disease revealed that 6-OHDA results in the p53-dependent death of dopaminergic cells, which was correlated with a decrease in Eag1 immunoreactivity (10,11). …”
Section: Introductionmentioning
confidence: 99%
“…This stimulation frequency-dependent Ca 2+ release indicates that the EAG1 channel plays a fine-tuning role in synaptic transmission during high-frequency firing when other potassium channels suffer cumulative inactivation [20]. In addition, the presence of EAG1 channels in the nigrostriatal pathway in the rat brain indicates that EAG1 channels may be involved in Parkinson's disease characterized by partial or complete loss of dopaminergic neurons [98]. The observations by Ferreira et al showed that both EAG1 channel and tyrosine hydroxylase immunoreactivity decreased in ipsilateral striatum in the neurotoxin 6-hydroxydopamine (6-OHDA) injected rats [98].…”
Section: Functions Of Eag1 Channels In Normal Neuronal Signalingmentioning
confidence: 99%
“…In addition, the presence of EAG1 channels in the nigrostriatal pathway in the rat brain indicates that EAG1 channels may be involved in Parkinson's disease characterized by partial or complete loss of dopaminergic neurons [98]. The observations by Ferreira et al showed that both EAG1 channel and tyrosine hydroxylase immunoreactivity decreased in ipsilateral striatum in the neurotoxin 6-hydroxydopamine (6-OHDA) injected rats [98]. On the basis that the reactive oxygen species (ROS), such as the superoxide anion and H 2 O 2 , mediate the cytotoxicity of dopaminergic neurons by 6-OHDA [99] and EAG1 channels are greatly sensitive to H 2 O 2 modification [31], it will be worth exploring the physiological roles of EAG1 channels in dopaminergic midbrain neurons as well as in Parkinson's disease.…”
Section: Functions Of Eag1 Channels In Normal Neuronal Signalingmentioning
confidence: 99%